Toward an Interdisciplinary 3D Animation Design Process for Palaeoart: Visualising Quaternary Megafauna From Sri Lanka’s Sabaragamuwa Basin - Kennedy, Jason; Sumanarathna, Aravinda Ravibhanu (Coquina Press, 2026)
This study examines the use of 3D animation workflows to create scientifically credible palaeoart of extinct Quaternary megafauna from Sri Lanka’s Sabaragamuwa Basin. While palaeoart has long played a critical role in visualising prehistoric life, its scientific foundations are often under-reported, and visual reconstructions are rarely subjected to peer review – especially in underrepresented regions like Sri Lanka. There remains a significant gap in both the availability and methodological transparency of palaeoart, despite increasing international calls for standardised and evidence-based practices in the field. This research presents the first photorealistic 3D reconstructions of two extinct Sri Lankan megafauna: Palaeoloxodon namadicus sinhaleyus and Quaternary rhinoceros material historically referred to as Rhinoceros sinhaleyus. These visualisations were produced through interdisciplinary collaboration between a palaeontologist and digital artist team, merging morphometric data of Ratnapuran fauna with animation and visual effects pipelines. By documenting the full design process and clarifying the scientific and aesthetic decisions involved, this study provides a model for future scientist-palaeoartist collaboration and highlights the communicative power of digital visualisation to enhance public engagement with underexplored palaeontological heritage.
Keywords: 370506 Palaeontology (incl. palynology); 360502 Computer gaming and animation; 370905 Quaternary environments; 360506 Visual effects; 460807 Information visualisation; 0403 Geology; 0602 Ecology; 2101 Archaeology; Paleontology; 3103 Ecology; 3104 Evolutionary biology; 3705 Geology